Panchmakaar for Aushadhi in Mantrachikitsa - A Review (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda considers only 3 Aushadhi Daivavyapashray (taking refuge of your Aatma (soul)), Yukti Vyapashraya (how one can immediately bring relief to patient Yukti (idea)), Sattvavajay (purity of thoughts). Daivavyapashraya Chikitsa includes all Mantra Chikitsa in Ayurveda for healing Doshas caused due to past life Karmas. Our Aatma is Drishta of all our Karmas in a lifespan. Aatma is connected with Parmatma. Invocation of Parmatma is done through Mantras. Mantra is a broader term with its application under Vedic Texts, Tantrik Texts, Tarka Shastra, Yagya & Tapa. Mantra as a concept is often misunderstood that it only connected with Tantra. Tantra is not appreciated because of Panch Makaar. This review will highlight the Correct Panchmakaar and why so it was consumed as Aushadhi. Since Mantra is invocation of divine under different approach systems. The Rishis who were called Mantra Drishta highlights the importance of concept creation over language. This review will help in establishing the importance of Panchmakaar as Aushadhi for Mantra Chikitsa under Ayurveda for treatment of diseases/disorders. Removing confusion and pursue healthy spiritual journey is the purpose of this research paper. This controversial subject of Panchmakar was the major reason for avoiding spiritualist/ Tantriks (those seeking path of spirituality). These misinterpretations created Bhram though it was supposed to connect with Brahma. Panch Makaar's were widely misunderstood and misinterpreted by all.